The field test results of geometric-force method for track state estimation - Kossov, V. S.; Bidulya, A. L.; Krasnov, O. G.; Akashev, M. G. (Science and Transport Progress, 2013)
Purpose. Study the possibility of using geometrically-force method to determine sections of high risk of derailment in railway stations at empty wagons movement. In the test program track diagnosing subject to longitudinal forces in the freight train effecting empty wagons is provided. Methodology. To this effect empty mineral wagon and thermal cistern were equipped with strain-gauge wheel sets, strain-gauge automatic coupler and other instruments, set in the freight train weighing 4500 t. Findings. In the course of this work it was ascertained that the geometric-force ethod gives possibility to receive additional information about the track condition from the position of empty cars stability against derailment. It is shown that some sections of high risk of derailment pieces of line does not discarded by traditional ways, based on an assessment of the geometric parameters of the way. Those track sections are identified by this method, which can not be evaluated by technical means, used currently on track measurement cars. Pieces of line with low parameters on empty cars stability against derailment are individual and they are determined not only by the sizes of deviations, but their form, a combination of different types of roughness, profile and defective elements of the permanent way. Originality. Geometric-force method should be considered as complementary to the existing technology assessment of the way on the geometrical parameters; its implementation will allow revealing the track section, dangerous for the motion of empty wagons. Practical value. For the geometrically-force method realization of assessment of the way in the railway network of JSC «Russian Railways» it is proposed on the basis of the accumulated statistics and experimental data in accordance with wagons tests with a high center of gravity to develop specialized software for wagons through gauges to assess ways bygeometrically-force method that excludes the use in technology assessment of the additional freight wagon way with a strain-gauge wheel sets.